Obstacles and Efforts of Online English Learning In Elementary Schools - Musiman, Musiman; Prihatini, Candraning (Jurnal Basicedu, 2021)
The implementation of online learning in Indonesia due to Covid-19 pandemic raises problems for the schools, students, and parents. This research was done to reveal the real obstacles the schools, students, and parents face and the efforts they have done as the ways out of the obstacles. It is a descriptive qualitative research with 7Â  school principals, 7 English teachers, and 43 fifth graders with their parents as the subjects of the research. The result shows that all school principals and teachers (100%) mention that they find it difficult to control the students. Eighty percent teachers mentioned that they find it difficult to explain the material. It is difficult for students to understand the lesson was mentioned by 64% students. Facing those obstacles, school principals, teachers, students, and parents have done some efforts as the ways out. Their efforts, however still do not solve all the obstacles yet. Thus, if all the obstacles of online learning can be solved, the writers believe that online learning can be used as an alternative learning technique after the Covid-19 pandemic